Sexual and Reproductive Health Status of Adolescents in Nepal - Khanal, Prabha (Journal of Population and Development, 2020)
This article explores about the sexual and reproductive features of adolescence in the context of Nepal. Adolescence refers to the years of transition from childhood to adulthood. This study is a review based on secondary data source. Most of the data and information are carried out by demographic and health survey conducted by Ministry of Health and Population. Married adolescent 15-19 years of aged population are recognized as the study population for this study. The study finds the proportion of married adolescent women are decreased from 43 percent in 1996 to 27 percent in 2016. On the basis of sexual and reproductive health behavior of adolescent, female are more active than male. The result shows that the knowledge of family planning methods among adolescents are found universal. The demand of family planning seems to be insufficient to this group. The 15 percent of adolescents have utilized the family planning methods. The unmet need of family planning is higher in adolescent women than that of national level. The adolescent pregnancy is another serious problem. Nepal Demographic Health Survey 2016 states that 17 percent of adolescents are either mothers or are pregnant. This number was 43 percent in 1996. The trend of adolescent pregnancy seems to be decreasing. However, the sexual and reproductive health behavior of adolescent has become a social concern in developing countries like Nepal. In this way, the Nepalese government should prioritize in the contemporary issues of sexual and reproductive behavior of adolescents in the country.